Lesson Study: Engaging Collaborative Learning to Promote Teachers’ Pedagogical Competence - Siti Aimah; Bambang Purwanto; Heri Dwi Santoso; Muhimatul Ifadah (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Teacher quality is the most important factor in enhancing student achievement. In order to achieve the goal, lesson study comprises three main phases of plan, do, and see encourages teachers to do collaborative learning in which they create learning communities to discover, create, and negotiate new meanings to improve their teaching. Teachers at all stages of their careers could learn from one another. They could work together, discuss common teaching issues, share successful strategies, and develop new approaches to share problems. Organizing such networks of teacher in collaborative learning promotes an eﬀective way to share pedagogical and content knowledge. In order to think productively about ways to enhance student learning, teachers need to consider both the material they are teaching and the ways that they are presenting it. Considering the importance of both of them, this study aims to know the impact of collaborative learning to teacher performance particularly in SD/MI Al Hikmah Semarang. By involving three model teachers conducting teaching and learning process, and six observers (teachers and lecturers) observing the teacher performance and student activities in the classroom conducted in two cycles, this study shows that collaboration among teachers increased their performance of teaching in which teachers emphasized using active engagement, appropriate learning designs, and application of theories on learning. The majority of teachers agreed that collaborative learning through lesson study helped their performance of teaching. Teachers who participated in collaborative learning had better achievement in their teaching performance rather than those who did not participate in collaborative learning.